1991
DOI: 10.1038/349426a0
|View full text |Cite
|
Sign up to set email alerts
|

Raf-1 protein kinase is required for growth of induced NIH/3T3 cells

Abstract: Many growth factors regulate the cytoplasmic Raf-1 protein kinase, consistent with its having a central role in transduction of growth signals. The kinase is ubiquitously expressed and can promote proliferation, presumably in a manner dependent on growth-factor receptors and membrane-associated oncogenes. We have now examined the dependence of serum- and TPA (12-O-tetradecanoylphorbol-13-acetate)-regulated NIH/3T3 cell growth on RAF-1 kinase to determine whether Raf-1 is essential for receptor signalling. We i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
263
2
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 476 publications
(276 citation statements)
references
References 19 publications
10
263
2
1
Order By: Relevance
“…These results contrast dramatically with NIH3T3 cells, where activated Raf-1 or MEK alone is su cient to cause tumorigenic transformation (Kolch et al, 1991;Leevers et al, 1994;Stokoe et al, 1994;Cowley et al, 1994;Mansour et al, 1994). In the present study, we have demonstrated that MAPK activation is still necessary for Ras transformation (Figure 3).…”
Section: Farnesyltransferase Inhibitors Impair Ras- But Not Src- Trcontrasting
confidence: 82%
See 1 more Smart Citation
“…These results contrast dramatically with NIH3T3 cells, where activated Raf-1 or MEK alone is su cient to cause tumorigenic transformation (Kolch et al, 1991;Leevers et al, 1994;Stokoe et al, 1994;Cowley et al, 1994;Mansour et al, 1994). In the present study, we have demonstrated that MAPK activation is still necessary for Ras transformation (Figure 3).…”
Section: Farnesyltransferase Inhibitors Impair Ras- But Not Src- Trcontrasting
confidence: 82%
“…Raf-1 then stimulates MAPK kinases (MEK1 and MEK2), which in turn activate p42 and p44 MAPK. The important role of the Raf/MEK/MAPK pathway in Ras-mediated transformation of ®broblasts is supported by the observations that kinase-de®cient, dominant negative mutants of Raf-1, MEK and MAP kinases are potent inhibitors of Ras signal transduction and transformation (Kolch et al, 1991;Cowley et al, 1994;Meloche et al, 1992;Westwick et al, 1994;Troppmair et al, 1994;Brtva et al, 1995). Furthermore, since constitutively activated mutants of Raf-1 or MEK cause tumorigenic transformation of NIH3T3 cells (Kolch et al, 1991;Leevers et al, 1994;Stokoe et al, 1994;Cowley et al, 1994;Mansour et al, 1994), activation of the Raf-1/MEK/MAPK pathway alone is believed to be su cient to mediate Ras transformation.…”
Section: Introductionmentioning
confidence: 95%
“…ERK1 can be stimulated by the sequential activation of Ras-c-Raf-1-MEK1 (Kolch et al, 1991;Huang et al, 1993;Crews et al, 1992;Minden et al, 1994). Indeed, the observations that u-PAR expression was reduced by interfering with MEK1 and c-Raf-1 is consistent with the notion that the initial stimulus lies upstream of c-Raf-1.…”
Section: Discussionsupporting
confidence: 68%
“…These MAPKs are activated by phosphorylation on threonine and tyrosine residues by a dual activity kinase MEK1 (Crews et al, 1992). The dual activity kinase is, in turn, phosphorylated by the serine-threonine kinase c-Raf-1 (Huang et al, 1993;Kyriakis et al, 1992;Jelinek et al, 1994) the activity of which is determined by homodimerization (Farrar et al, 1996), Ras (Kolch et al, 1991), Protein Kinase C (Sozeri et al, 1992) and membrane phosphatases (Dent et al, 1995). We show, for the ®rst time, that the elevated expression of the u-PAR gene in a colon cancer cell line (RKO) is largely a consequence of a constitutively activated ERK1-dependent signal transduction pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we found that the kinase-inactive JNK1 expression construct countered the stimulation of u-PAR promoter activity by c-Ha-Ras (Figure 9c) with an equimolar amount of the dominant negative plasmid resulting in over 65% inhibition compared with the empty vector (SRa Vector). Taken together, these results suggest that while c-Ha-ras can activate multiple downstream signaling cascades (Deng and Karin 1995;RodriguezViciana et al, 1994;Russell et al, 1995;Kolch et al, 1991), u-PAR promoter activity in OVCAR-3 cells is regulated by this oncogene partly through a JNKdependent signaling module.…”
Section: The Stimulation Of U-par Promoter Activity By the Expressionmentioning
confidence: 82%